Alcohol and Caffeine Co-Administration Increased Acetylcholinesterase Activity and Inflammatory Cytokines in Sleep-Deprived Rats: Implications for Cognitive Decline and Depressive-Like Manifestations - Daubry, Tarela Melish Elias; Nwogueze, Bartholomew Chukwuebuka; Toloyai, Pere-Ebi Yabrade; Moke, Emuesiri Goodies (Sleep Science, 2024)
Sleep deprivation is a major health problem in modern society; it has been worsened by alcohol and caffeine intake to stay awake and improve bodily activities, an experience common among night-shift workers. For the present study, 50 adult male Wistar rats weighing between 150 g and 200 g were randomly selected and divided into 5 groups of 10 rats each (n = 10). Group 1 was the control group; group 2 was the group of sleep-deprived (SD) rats; group 3 was composed SD rats submitted to the administration of 20% alcohol; group 4 comprised SD rats submitted to the administration of 200 mg/kg of caffeine; and Group 5 was composed of SD rats who underwent the co-administration of 20% alcohol and 200 mg/kg of caffeine. At the end of 28 days, the animals were euthanized, and blood samples were collected for biochemical analysis. Memory, anxiety, social behavior and locomotive activity were assessed using the Y-maze, the elevated plus maze, the hole-board and three-chambered social approach tests, and the open field test. The plasma levels of the acetylcholinesterase (AChE) enzyme and inflammatory cytokines (interleukin 6 [IL-6], interleukin 10 [IL-10], and tumor necrosis factor beta, [TNF-β]) were also measured. Data was expressed as mean ± standard error of the mean [SEM] values, and the data were analyzed through analysis of variance (ANOVA) followed by the Tukey post hoc test, with significance set at p < 0.05. The results revealed that sleep deprivation, and the co-administration of alcohol and caffeine impair memory in rats. Sleep deprivation also caused a significant increase in anxiety and anxiety-related behavior, with decreased social interaction, in rats. Locomotive activity was improved in SD rats, especially in those to which alcohol was administered. Sleep deprivation significantly reduced acetylcholinesterase activity among SD rats and those to which alcohol was administered when compared with the controls. The plasma levels of IL-6, IL-10 and TNF-β were significantly increased in SD rats when compared with the controls. The administration of alcohol and caffeine separately, as well as their co-administration, significantly increased cytokine levels in rats.
Keywords: sleep deprivation; alcohol; caffeine; inflammatory cytokines; acetylcholinesterase activity